2019
DOI: 10.20944/preprints201905.0278.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melanopsin<sup>+</sup>RGCs Are Fully Resistant to NMDA-Induced Excitotoxicity

Abstract: We studied short- and long-term effects of intravitreal injection of N-methyl-D-aspartate (NMDA) on melanopsin-containing (m+) and non-melanopsin-containing (Brn3a+) retinal ganglion cells (RGCs). In adult SD-rats, the left eye received &nbsp;a single intravitreal injection of 5&micro;L of 100nM NMDA. At 3 and 15 months, retinal thickness was measured in vivo using SD-OCT.&nbsp; Ex vivo analyses were done at 3, 7, 14 days or 15 months after damage. Whole-mounted retinas were immunolabelled for Brn3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…It has been documented that ONs-αRGCs are a type of intrinsically photosensitive ganglion cells, the M4-ipRGCs (Ecker et al, 2010;Schmidt et al, 2014;Sonoda et al, 2020). However, these cells are not easy to identify with the classical OPN4 antibody against melanopsin, which identifies M1, M2, and M3 ipRGCs, as they do not express sufficient melanopsin photopigment (Vidal-Villegas et al, 2019, 2021a, although their functional dependence on pigment has been characterized (Estevez et al, 2012), which has led to a lack of global consensus on the overall identification of the total M4-ipRGC population and the number of cells per retina in rodents. It has recently been reported that cells expressing the photopigment also express the transcription factor T brain 2 (Tbr2), which is crucial for the maintenance of these cells (Berg et al, 2019;Tran et al, 2019;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that ONs-αRGCs are a type of intrinsically photosensitive ganglion cells, the M4-ipRGCs (Ecker et al, 2010;Schmidt et al, 2014;Sonoda et al, 2020). However, these cells are not easy to identify with the classical OPN4 antibody against melanopsin, which identifies M1, M2, and M3 ipRGCs, as they do not express sufficient melanopsin photopigment (Vidal-Villegas et al, 2019, 2021a, although their functional dependence on pigment has been characterized (Estevez et al, 2012), which has led to a lack of global consensus on the overall identification of the total M4-ipRGC population and the number of cells per retina in rodents. It has recently been reported that cells expressing the photopigment also express the transcription factor T brain 2 (Tbr2), which is crucial for the maintenance of these cells (Berg et al, 2019;Tran et al, 2019;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%